Strategi Marketing Public Relations, Persatuan Panahan Indonesia (PERPANI) dalam Mengembangkan Olahraga Panahan di Kalangan Remaja - Ary Koeswiranto; Oktaviana Purnamasari (PROPAGANDA, 2022)
Indonesian Archery Association (PERPANI) is the national organization of the sport of archery. Archery is an Olympic sport that should be competed in every Olympic Games. Indonesia has the opportunity to win a medal at the Olympics because it has won a silver medal which was the first medal for Indonesia at the 1988 Olympics. The main challenge for the Indonesian Archery Association (PERPANI) is the slow regeneration of outstanding athletes. The phenomenon that entering the world of sports as a profession for teenagers is still considered a field that cannot promise a good future. This study aims to identify and analyze the marketing public relations Strategy of the Indonesian Archery Association (PERPANI) in developing archery among teenagers. The theory used in this research is Thomas L Harris' Three Ways Strategy, namely Push, Pull and Pass and Major Tools of Marketing Public Relations Phillip Kotler & Kevin Lane Keller. The Indonesian Archery Association (PERPANI) applies Push, Pull and Push strategies, including by: (a). Produce a movie (Film) entitled 3 Srikandi, about the struggle of the trio of Three Indonesian womens archer to get Indonesia's first medal in the Olympics; (b). Invite important figures, one of which is the President as one of the participants in the archery competition; (c). Incorporating archery scenes in the opening ceremony of the Asean Para Games (Opening Ceremony of the Asian Para Games); (d). Organizing the Olympic Movement In Actions. This study uses a qualitative approach with a qualitative descriptive method using a paradigm. The research data were obtained through in-depth interview techniques. Sources of data or informants are structural officials at the Indonesian Archery Association, technical data analysis using analysis from Mile and Huberman. The Indonesian Archery Association also implements Major Tools of Marketing Public Relations which consists of Publications, events, sponsorship, news, speeches, public services, identity media, event activities are activities that greatly affect the target.